Proposal to New Jersey Department of Health for Modification of New Employees’ Orientation (Journal of Organizational Psychology, 2020)
This paper is about a program proposal for New Jersey Department of Health to find an alternative way to conduct their orientation training to be appropriate for adult learners, and to meet the four key elements of learning- motivation, reinforcement, retention, and transference. The proposed project will train New Jersey educators how to modify the orientation training using the adult learning principles of Knowles’ Andragogy to help them to design the teaching methodologies that are useful for adults from different educational, cultural and developmental backgrounds. The proposed program will consist of the basic phases of program planning include needs assessment, program outcomes and learning objectives, transfer of learning, program structure, and program evaluation. Two informal and one formal method or strategies for gathering data needs/ideas were designed. One informal and two formal methods or strategies for program evaluation data were also designed to determine the program effectiveness and future direction. The program structure, timeframe and resources were explained in detail. An instructional plan and program budget were developed and included.
Keywords: Organizational Psychology; helping others; aid; assistance; entitlement; toxic charity